Coherent speech as a subject of study in psychology, linguistics and psycholinguistics - E.N.Ziyodullaeva teacher (Zien Journals, 2023)
This article in psychology and linguistics studies the development of coherent speech in children with intellectual disabilities and highlights the problem of its development. It also talks about scientists who worked on coherent speech
Keywords: Connected speech; psychology; linguistics; thinking